Journalism, economic uncertainty and political irregularity in the digital and data era - Tong, Jingrong (Emerald Publishing Limited, 2022)
Complexities and dilemmas are evident in journalism in the digital and data age. Scarcity of audiences' attention jeopardises the survival of information media in the market, technological penetration increasingly renders journalism a complex information system, and the rise of partisan journalism accompanies the crisis of objective reporting. Analysing the evolving industry as it turns to the help of digital technologies such as algorithms and cloud computing to reach and engage local and global audiences, Journalism, Economic Uncertainty and Political Irregularity in the Digital and Data Era explores the challenges journalism faces in great depth and detail. Tong discusses the transformation of quality journalism that has become high-tech, interdisciplinary, saturated with human interest, and sometimes even fiercely partisan under the influence of multiple disruptions brought about by digital technology, economic uncertainty, and political irregularity. A timely and important contribution to the research of journalism, Journalism, Economic Uncertainty and Political Irregularity in the Digital and Data Era bridges media with the fields of sociology, politics, technology, and culture studies - central for academics, writers and researchers.